2021
DOI: 10.1002/jsfa.11369
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of water–nitrogen coupling effects in paddy field based on ORYZA (v3) model

Abstract: BACKGROUND: Nitrogen and water are two major factors in rice production. Due to the lack of ample evidence and much uncertainty in field experiments, the coupling effects of water and nitrogen in paddy fields have remained debatable over recent years.RESULTS: A fine-calibrated ORYZA (v3) model was applied to simulate rice growth and development under different nitrogen (N) rates and irrigation regimes for a double rice-cropping system in South China. We designed a numerical experiment of 504 treatments, consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Water and nitrogen are important factors that limit crop growth and yield ( Gonzalez-Dugo et al., 2010 ; Darren et al., 2020 ; Tan et al., 2021 ). As a good solvent and carrier, water not only accelerates the dissolution and mineralization of nitrogen in soil but also transports it to crop roots in the form of diffusion or mass flow ( Crevoisier et al., 2010 ), which affects the availability of soil nitrogen and changes the absorption, transport, and assimilation of nitrogen by crops ( Guan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water and nitrogen are important factors that limit crop growth and yield ( Gonzalez-Dugo et al., 2010 ; Darren et al., 2020 ; Tan et al., 2021 ). As a good solvent and carrier, water not only accelerates the dissolution and mineralization of nitrogen in soil but also transports it to crop roots in the form of diffusion or mass flow ( Crevoisier et al., 2010 ), which affects the availability of soil nitrogen and changes the absorption, transport, and assimilation of nitrogen by crops ( Guan et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water and nitrogen fertilizer are the two main factors affecting apple growth and development . Nitrogen use efficiency of crop is constrained by water management . In order to improve yield farmers likes to apply a lot of synthetic N fertilizers and manure, but nitrogen uptake and utilization of crop are only less than half, and the surplus then causes an environment problem. , …”
Section: Introductionmentioning
confidence: 99%
“…7 Nitrogen use efficiency of crop is constrained by water management. 8 In order to improve yield farmers likes to apply a lot of synthetic N fertilizers and manure, but nitrogen uptake and utilization of crop are only less than half, and the surplus then causes an environment problem. 9,10 Nowadays, due to more and more consumers having high quality demand for fruits, the maintenance and improvement of fruit quality in the post-harvest storage is more and more important.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tan et al. (2022) evaluated the coupling impacts of water–N fertilizer on paddy rice growth and made the optimum N fertilizer application scheme and irrigation threshold and quota. Xu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have investigated the predictive performance of the ORYZA_V3 model for paddy rice growth. For example, Tan et al (2022) evaluated the coupling impacts of water-N fertilizer on paddy rice growth and made the optimum N fertilizer application scheme and irrigation threshold and quota. Xu et al (2018) found that the paddy rice biomass growth in the ORYZA_V3 model was sensitive to the water and N deficiency stress, and this crop model performed better for predicting paddy rice biomass under potential conditions than underwater and N-limited conditions.…”
Section: Introductionmentioning
confidence: 99%